Effect of Rainfall-Induced Soil Geochemistry Dynamics on Grassland Soil Microbial Communities - Cruz-Martínez, Karelyn (American Society for Microbiology, 2012)
In Mediterranean-type grassland ecosystems, the timing of rainfall events controls biogeochemical cycles, as well as the phenology and productivity of plants and animals. Here, we investigate the effect of short-term (days) soil environmental conditions on microbial community structure and composition during a natural wetting and drying cycle. Soil samples were collected from a meadow in Northern California at four time points after the first two rainfall events of the rainy season. We used 16S rRNA microarrays (PhyloChip) to track changes in bacterial and archaeal community composition. Microbial communities at time points 1 and 3 were significantly different than communities at time points 2 and 4. Based on ordination analysis, the available carbon, soil moisture, and temperature explained most of the variation in community structure. For the first time, a complementary and more comprehensive approach using linear regression and generalized logical networks were used to identify linear and nonlinear associations among environmental variables and with the relative abundance of subfamilies. Changes in soil moisture and available carbon were correlated with the relative abundance of many phyla. Only the phylum Actinobacteria showed a lineage-specific relationship to soil moisture but not to carbon or nitrogen. The results indicate that the use of a high taxonomic rank in correlations with nutritional indicators might obscure divergent subfamily-level responses to environmental parameters. An important implication of this research is that there is short-term variation in microbial community composition driven in part by rainfall fluctuation that may not be evident in long-term studies with coarser time resolution.